2008
DOI: 10.1152/ajprenal.00469.2007
|View full text |Cite
|
Sign up to set email alerts
|

Acid, basic, and neutral peptidases present different profiles in chromophobe renal cell carcinoma and in oncocytoma

Abstract: Renal cell carcinomas (RCCs) are neoplasias with high prevalence and mortality. We previously reported that several peptidases may be involved in the pathophysiology of clear cell renal cell carcinoma (CCRCC). Now, to gain insight into the reasons that lead the various RCC types to behave very differently with regard to aggressiveness and response to anticancer treatments, we analyzed subsets of chromophobe renal cell carcinoma (ChRCC), and renal oncocytoma (RO), a benign tumor; as well as different grades and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 35 publications
4
22
1
Order By: Relevance
“…We observed that the activity of some peptidases like APN, CAP, and DPPIV was increased in high-grade and advanced stage CCRCC (4,27,29,59). In this work, we show that 5-yr survival of patients with CCRCC was shorter if the activity of these three peptidases was high.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…We observed that the activity of some peptidases like APN, CAP, and DPPIV was increased in high-grade and advanced stage CCRCC (4,27,29,59). In this work, we show that 5-yr survival of patients with CCRCC was shorter if the activity of these three peptidases was high.…”
Section: Discussionsupporting
confidence: 49%
“…Our previous studies (4, 5, 27-29, 58, 59) have demonstrated that the activity, protein expression, and mRNA levels of these three and other peptidases are selectively altered in several subtypes of renal cell neoplasms (CCRCC, papillary renal cell carcinoma, chromophobe renal cell carcinoma, and renal oncocytoma). What is more, we have found that several peptidase activities are significantly increased in high-stage and high-grade CCRCC, suggesting the involvement of these enzymes in the biological aggressiveness of these neoplasms (4,27,29,59).…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…In addition, it has been reported that the activity of different cytosolic peptidases such as puromycin-sensitive aminopeptidase (PSA or EC 3.4.11.14), aminopeptidase B (APB or EC 3.4.11.6) and pyroglutamyl-peptidase I (PGI or EC 3.4.19.3) was altered in breast 19,20, kidney 21,22 and thyroid tumors 23.…”
Section: Introductionmentioning
confidence: 99%
“…ACE and ACE2 are expressed in renal tubules and play an essential role in the regulation of the renin-angiotensin system at the local level [15]. Impairment of this system has been studied in various noncancerous kidney diseases [12,[16][17][18], and several types of renal cell carcinomas and oncocytomas [19][20][21].…”
Section: The Renin-angiotensin Systemmentioning
confidence: 99%